Investigation of faecal volatile organic metabolites as novel diagnostic biomarkers in inflammatory bowel disease. Issue 5 (25th January 2016) - Ahmed, I.; Greenwood, R.; Costello, B.; Ratcliffe, N.; Probert, C. S.
Summary: Background: The aetiology of inflammatory bowel disease (IBD) remains poorly understood. Recent evidence suggests an important role of gut microbial dysbiosis in IBD, and this may be associated with changes in faecal volatile organic metabolites (VOMs). Aim: To describe the changes in the faecal VOMs of patients with IBD and establish their diagnostic potential as non‐invasive biomarkers. Methods: Faecal samples were obtained from 117 people with Crohn's disease (CD), 100 with ulcerative colitis (UC), and 109 healthy controls. Faecal VOMs were extracted using solid‐phase micro‐extraction and analysed by gas chromatography mass spectrometry. Data analysis was carried out using partial least squares‐discriminate analysis (PLS‐DA) to determine class membership based on distinct metabolomic profiles. Results: The PLS‐DA model showed clear separation of active CD from inactive disease and healthy controls ( P < 0.001). Heptanal, 1‐octen‐3‐ol, 2‐piperidinone and 6‐methyl‐2‐heptanone were up‐regulated in the active CD group [variable important in projection (VIP) score 2.8, 2.7, 2.6 and 2.4, respectively], while methanethiol, 3‐methyl‐phenol, short‐chain fatty acids and ester derivatives were found to be less abundant (VIP score of 3.5, 2.6, 1.5 and 1.2, respectively). The PLS‐DA model also separated patients with small bowel CD from healthy controls and those with colonic CD from UC ( P < 0.001). In contrast, less distinct separation was observed between active UC, inactive UC and healthy controls. Conclusions: Analysis of faecal volatile organic metabolites can provide an understanding of gut metabolomic changes in IBD. It has the potential to provide a non‐invasive means of diagnosing IBD, and can differentiate between UC and CD.